Designing IoT-Based Camera on the House Doors for Securing the House - Novi Herawadi Sudibyo; Zaidir Jamal; Abdi Darmawan; Suspiana Suspiana (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Doors were the first access when entering a room or house. The access of the doors (e.g., office and house doors) should have been given only for certain people. The security system on the doors was very important because it was accessible only for the persons who had authorization. In this study, the security system was built through RFID as a substitute for a house key, a camera as a recorder around the front door of the house, and the camera canals as a controller to capture real time through the telegram application. In the remote control system (IoT) application, there were several menus or commands with different functions that met the needs of the system and the user. Command "/start" was used to activate and connect security applications and systems, command "/portrait" was used to capture conditions around the door, command "/close" was used as a command to lock the door, and command"/open" was used to lock the door.Keywords:Camera, RFID, Nod Mcu, Telegram, and Home Security